Insights into the resistance and resilience of the soil microbial community. Issue 2 (1st June 2012) - Griffiths, Bryan S.; Philippot, Laurent
Abstract Soil is increasingly under environmental pressures that alter its capacity to fulfil essential ecosystem services. To maintain these crucial soil functions, it is important to know how soil microorganisms respond to disturbance or environmental change. Here, we summarize the recent progress in understanding the resistance and resilience (stability) of soil microbial communities and discuss the underlying mechanisms of soil biological stability together with the factors affecting it. Biological stability is not solely owing to the structure or diversity of the microbial community but is linked to a range of other vegetation and soil properties including aggregation and substrate quality. We suggest that resistance and resilience are governed by soil physico‐chemical structure through its effect on microbial community composition and physiology, but that there is no general response to disturbance because stability is particular to the disturbance and soil history. Soil stability results from a combination of biotic and abiotic soil characteristics and so could provide a quantitative measure of soil health that can be translated into practice.